Lassa fever prevention in Nigeria: A study of a multi-disciplinary mix of healthcare workers in a referral treatment centre in Nigeria - Osarhiemen Iyare; Sadiku Saidu; Chukwuma David Umeokonkwo; Ijeoma Nkem Okedo-Alex; Sandra Chizoba Mba; Abdulhakeem Abayomi Olorukooba (Journal of Interventional Epidemiology and Public Health)
ntroduction: Healthcare workers (HCWs) are especially susceptible to Lassa fever (LF) due to the close contact they have with patients. Ebonyi State is endemic for Lassa Fever with recurrent outbreaks that have had catastrophic affectation on health workers constantly at risk of this infection. This study aimed to determine knowledge, attitude and practice toward Lassa fever prevention and control in a tertiary hospital in Ebonyi State Nigeria.